2016
DOI: 10.1111/1462-2920.13591
|View full text |Cite
|
Sign up to set email alerts
|

Microbial processes of the carbon and sulfur cycles in an ice‐covered, iron‐rich meromictic lake Svetloe (Arkhangelsk region, Russia)

Abstract: Biogeochemical, isotope geochemical and microbiological investigation of Lake Svetloe (White Sea basin), a meromictic freshwater was carried out in April 2014, when ice thickness was ∼0.5 m, and the ice-covered water column contained oxygen to 23 m depth. Below, the anoxic water column contained ferrous iron (up to 240 μμM), manganese (60 μM), sulfide (up to 2 μM) and dissolved methane (960 μM). The highest abundance of microbial cells revealed by epifluorescence microscopy was found in the chemocline (redox z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 58 publications
2
61
0
Order By: Relevance
“…These lakes include Lake Matano (Indonesia; Crowe et al, ), Lake La Cruz (Spain; Walter et al, ), Lake Pavin (France; Viollier et al, ; Lehours et al, ), and the ferruginous Kabuno Bay within Lake Kivu (Democratic Republic of Congo; Llirós et al, ). The analog utility of these lakes seems to be spurring discovery or recognition of additional geographically diverse lakes as ferruginous (e.g., Savvichev et al, ). The presence of anoxic and ferruginous conditions in the bottom waters of lakes, which either do not turn over at all, or turn over regularly or occasionally, may not be that rare.…”
Section: Introductionmentioning
confidence: 99%
“…These lakes include Lake Matano (Indonesia; Crowe et al, ), Lake La Cruz (Spain; Walter et al, ), Lake Pavin (France; Viollier et al, ; Lehours et al, ), and the ferruginous Kabuno Bay within Lake Kivu (Democratic Republic of Congo; Llirós et al, ). The analog utility of these lakes seems to be spurring discovery or recognition of additional geographically diverse lakes as ferruginous (e.g., Savvichev et al, ). The presence of anoxic and ferruginous conditions in the bottom waters of lakes, which either do not turn over at all, or turn over regularly or occasionally, may not be that rare.…”
Section: Introductionmentioning
confidence: 99%
“…While relative abundance of organisms does not necessarily correspond to biogeochemical activity, these observations provide circumstantial evidence for further studies to investigate the relationship between methanogens and pelagic CH 4 production. Furthermore, water column methanogenesis has been noted at Lake Matano (Crowe et al, ) and Lake Svetloe, although rates were two orders of magnitude less than rates measured in the sediment (Savvichev et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…Crowe et al () suggested that Fe(III)‐bearing minerals may be resistant to microbial reduction in ferruginous systems, and our data support this. A precedent for the dominant role of methanogenesis in organic carbon degradation has also been put forward by the activity measurements of different anaerobic pathways in ferruginous Lake Matano and Lake Svetloe (Crowe et al, ; Savvichev et al, ), and similar work would be useful in Brownie and Canyon Lakes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations